PHARMACOGNOSTIC AND HPTLC BASED COMPARATIVE STUDY ON LEAVES OF MERREMIA EMARGINATA BURM. F. AND CENTELLA ASIATICA (L.) URBAN - K. C., MANJU; JOHN, ANITHA; A., SAKKEENA; V., GAYATHRI DEVI; B., NEETHU KANNAN; A., KANAGARAJAN (International Journal of Current Pharmaceutical Research, 2019)
Objective: In this study, an attempt was made to generate information based on botanical, physicochemical and HPTLC data needed for proper identification and authentication of M. emarginata and C. asiatica belonging to two different families. Methods: Botanical study comprises of macroscopy, microscopy and powder microscopy of leaves of both crude drugs. The physicochemical parameters such as water-soluble extractive, alcohol soluble extractive and loss on drying at 105℃, total ash, acid insoluble ash, and volatile oil were determined according to standard methods. HPTLC studies of chloroform extracts of leaves of both drugs were conducted at 254 nm, 366 nm and 575 nm after derivatisation using vanillin-sulphuric acid and the results were documented. Results: The present study reveals that microscopy and most of the physicochemical parameters of both the plant materials are different. Anatomy of the leaves showed two main characteristic differences. First plenty of trichome with trichome base and calcium oxalate crystal is common in M. emarginata, which is not observed in C. asiatica. Both plants have different venation patterns and leaf constants. The total ash content and the solubility in alcohol and water for leaves of C. asiatica are higher than that of M. emarginata. The HPTLC fingerprinting pattern obtained for both drugs are different. Conclusion: All the results obtained from this study help in determining differences and similarities of leaves of M. emarginata and C. asiatica and thereby preventing adulteration and substitution and emphasizing the importance of standardization.